Clinical application of a body area network-based smart bracelet for pre-hospital trauma care - Han, Wei; Yuan, Jin-Yang; Li, Rui; Yang, Le; Fang, Jia-Qin; Fan, Hao-Jun; Hou, Shi-Ke (Frontiers in Medicine, 2023)
Objective: This study aims to explore the efficiency and effectiveness of a body area networkbased smart bracelet for trauma care prior to hospitalization.To test the efficacy of the bracelet, an observational cohort study was conducted on the clinical data of 140 trauma patients pre-admission to the hospital. This study was divided into an experimental group receiving smart bracelets and a control group receiving conventional treatment.Both groups were randomized using a random number table. The primary variables of this study were as follows: time to first administration of life-saving intervention, time to first administration of blood transfusion, time to first administration of hemostatic drugs, and mortality rates within 24 hours and 28 days post-admission to the hospital. The secondary outcomes included the amount of time before trauma team activation and the overall length of patient stay in the emergency room.The measurement results for both the emergency smart bracelet as well as traditional equipment showed high levels of consistency and accuracy. In terms of pre-hospital emergency life-saving intervention, there was no significant statistical difference in the mortality rates between both groups within 224 hours post-admission to the hospital or after 28-days of treatment in the emergency department. Furthermore, the treatment efficiency for the group of patients wearing smart bracelets was significantly better than that of the control group with regard to both the primary and secondary outcomes of this study . These results indicate that this smart bracelet has the potential to improve the efficiency and effectiveness of trauma care and treatment.: A body area network-based smart bracelet combined with remote 5G technology can assist the administration of emergency care to trauma patients prior to hospital admission, shorten the timeframe in which life-saving interventions are initiated, and allow for a quick trauma team response as well as increased efficiency upon administration of emergency care.